1905
DOI: 10.1002/aja.1000040303
|View full text |Cite
|
Sign up to set email alerts
|

A composite study of the subclavian artery in man

Abstract: WITH ' 7 FIQTJBES AND 18 TABLES.Several years ago Hitzrot made a study of the axillary artery based upon records made in the Anatomical Laboratory of the Johns Hopkins University. To supplement this, the following study of the subclavian artery was made at the suggestion of Dr. Harrison. The clinical features relating to the artery are given in another article.'That there is need for further data concerning the ramifications of this artery is apparent when the accompanying figures, taken from a number of unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1924
1924
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…This would be an expression of an evolutionary process which, owing to the relatively high incidence of the LCA (30.1% of cases at intraoperative survey, 24.3% of which are bilateral) (Sutherland and Desai, 2000), is not fully concluded up to now. Indeed, cases in which a long LCA extending over six or more intercostal spaces and as large as the ITA (Kropp, 1951;Testut and Latarjet, 1972;Henriquez-Pino et al, 1997) and reaching the diaphragm (Bean, 1905;DeGaris, 1924) have been reported, further supporting the above hypothesis. In fact, if a LCA has the same caliber as the ITA, both arteries should be considered as branches of a common trunk.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This would be an expression of an evolutionary process which, owing to the relatively high incidence of the LCA (30.1% of cases at intraoperative survey, 24.3% of which are bilateral) (Sutherland and Desai, 2000), is not fully concluded up to now. Indeed, cases in which a long LCA extending over six or more intercostal spaces and as large as the ITA (Kropp, 1951;Testut and Latarjet, 1972;Henriquez-Pino et al, 1997) and reaching the diaphragm (Bean, 1905;DeGaris, 1924) have been reported, further supporting the above hypothesis. In fact, if a LCA has the same caliber as the ITA, both arteries should be considered as branches of a common trunk.…”
Section: Discussionmentioning
confidence: 58%
“…In humans the ITA shows different origin from the subclavian artery, even indirect, via a common trunk with other branches (Bean, 1905;Henriquez-Pino et al, 1993. In humans a different origin could be analogous to that normal in some mammals, but, to our knowledge, this was not proved.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…28) These results show that this Type d, appearing in more than half of the total, is remarkably common among whites, whereas it only appears in approximately 10% of Asians, including fetuses. The incidence of Type g, which is a form of Type c lacking Ss, has been reported to be only 0-4% in whites and negroes, 7,12,13,29,35,44) in contrast to the finding of 20% in Asians,27'*) indicating that it is a type appearing more commonly in Asians. In our study, we found that Type a, which exhibits a common trunk formed by Ca and Tif only, appeared with an incidence of 11.1% , but has been little reported by other researchers.…”
Section: Discussionmentioning
confidence: 98%
“…5,6,10,26) There have been numerous reports of substantial individual and racial differences in the position of arterial branches and the nature of their ramifications as a result of various factors that have an influence on morphosis. 7,12,13,17,21,27,29,33,35,44) However, there are almost no reports of studies that have attempted to characterize and classify the ramification and positions of the entire array of branches arising from the subclavian artery. The only relevant reports in Japan were those by Adachi (28)1) and Ouchi ('63)3°), who described the subclavian artery ramification in Japanese adults, and that by Mori (P41)28), who described Japanese fetuses.…”
mentioning
confidence: 99%